Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Pada Siswa SMK Bahana Mandiri 2 Kota Bekasi - Putri Anjaningsih; Heri Suhendri; Arfatin Nurrahmah (CV Putra Publisher, 2022)
Education is one of the most closely related issues with the development and progress of a nation. The education must be able to produce change and be able to develop nation's life. This is due to the forward or backward nation and state are influenced by the quality of human resources. Indonesia also has the same view of the importance of education in the progress of a nation.